Growth and Competitiveness as Factors of Eurozone External Imbalances : Evidence and Policy Implications - Diaz Sanchez, Jose Luis; Varoudakis, Aristomene (World Bank, Washington, DC, 2014)
The paper assesses the contribution of key factors associated with external imbalances in the Eurozone through the estimation of a panel-data vector autoregressive model over 1975-2011. Growth fluctuations, initially associated with demand booms triggered by unusually low interest rates and later with demand contractions resulting from the crisis and policy adjustments, have been key drivers of current account fluctuations. Changes in competitiveness, measured by real exchange rates or unit labor costs, have played a less important role. Demand shocks have contributed more to current account balance dynamics in the Eurozone periphery than in the core, whereas competitiveness has been a less prominent factor in the periphery but relatively more important in the core. Changes in competitiveness are positively associated with changes in growth. Preventing imbalances from building up in a context of growing financial integration and easy finance warrants enhanced mutual surveillance of fiscal imbalances, but also better regulation of credit markets to prevent excess leverage and concentration of lending in investments prone to speculative bubbles. Coordination of fiscal policy across the Eurozone would facilitate the management of external imbalances without placing an often unwarranted burden on fiscal tightening in countries with sound fiscal positions affected by credit booms. The policies of internal devaluation implemented in the periphery, aimed at promoting external competitiveness, may have had only limited effectiveness in restoring the external balance to equilibrium.